The Influence of Folktales on the Teaching and Learning of English Language in Secondary Schools in Rukungiri Municipality South- Western Uganda. - Ndyamuhaki, Eulyne (Kabale University, 2024)
Little effort has been taken to scientifically document and find out the influence of folktales on the teaching and learning of the English language. The content of some folktales has a clear historical gap with today's real life. The use of folktales in secondary schools is difficult to attract students' interest hence, affecting the learning of the English language in secondary schools. The purpose of this study was therefore investigate the influence of folktales on the teaching and learning of the English language in Secondary Schools in Rukungiri Municipality. The study was guided by specific objectives which include investigating the role of folktales in the teaching and learning of the English language and assessing the methods used in teaching and learning of English language in secondary schools in Rukungiri Municipality. The study employed a mixed research design utilizing both qualitative and quantitative research designs. Using simple random and purposive sampling techniques, a total of 109 respondents were selected to participate in the study. Questionnaires, interviews, and observation methods of data collection were used in this study. The result of this study indicated that the role of folktales in the teaching and learning of the English language in secondary schools in Rukungiri Municipality was enhancing extensive reading represented by 37%, improved academic performance by 20%, folktales promoted language education by 18%, it promotes ethnic characters 16% and developing students' ability in effective decision-making 9%. It was also found that the methods used in teaching and learning of English language in secondary schools included; direct method of teaching 32%, teaching-centered learning 28%, student-centered learning 24%, and communicative language teaching 16% respectively. It was also recommended that teachers should encourage students to continue with folktales in teaching and learning of English language to improve the academic performance of the students.